A comparison of multiphasic oral contraceptives containing norgestimate or desogestrel in acne treatment: A randomized trial - Jaisamrarn,U. (Elsevier USA, 2015)
© 2014 Elsevier Inc. All rights reserved. Objective: This study aimed to compare the effectiveness and safety of triphasic combined oral contraceptives (OCs) containing ethinyl estradiol (EE) and norgestimate (NGM) and biphasic combined OCs containing EE and desogestrel (DSG) in the treatment of mild to moderate acne. Study design: This was an investigator-blinded, randomized, parallel group trial conducted at 3 centers in Thailand. Female subjects 18-45 years old were assigned to one or the other OCs and evaluated for efficacy and safety parameters at the baseline visit and after 1, 3 and 6 months of treatment. Results: Among 201 randomized subjects, data from 93 subjects in the EE/NGM group and 95 subjects in the EE/DSG group were analyzed. After 6 months of treatment with EE/NGM and EE/DSG, no differences between formulations were found for the decrease in total acne lesion counts (74.4% vs. 65.1%, respectively, p=.070) or facial improvement score. More women using EE/NGM showed a decrease in severity of facial seborrhea than those using EE/DSG (p=.005). No changes in weight were noted in either group as compared to baseline. Conclusion: Multiphasic OCs containing EE/NGM and EE/DSG provided comparable efficacy and tolerability in the treatment of acne. However, EE/NGM had a more beneficial effect on facial seborrhea reduction than EE/DSG. Implications: EE/NGM and EE/DSG are multiphasic OCs, which were shown to be clinically equally effective for mild to moderate facial acne, and the multiphasic combined OC with NGM was more effective for women with facial seborrhea. Clinicians may apply the results of this study when considering treatment options for facial acne and seborrhea.